PRODUCTION OF CHLORINE GAS (Cl2) AND SODIUM HYDROXIDE (NaOH) FROM THE PURIFICATION OF ACEH SALT: A Review Article - Ridwan, R; Zaini, Halim (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT Jangka salt contains NaCl, CaCl₂, MgCl₂, CaSO₄, MgSO₄, Na₂SO₄, H₂O, dust, soil, and fine sand, with NaCl content of less than 78%, categorizing it as low-quality salt. This salt can be refined to increase its NaCl content to 92%-100% through gradual physical and chemical purification processes, as well as using ion-exchange resin, resulting in high-quality salt. One of the advantages of high-quality salt is its use as a raw material for producing chlorine gas and sodium hydroxide through the electrolysis process. The results can be used in various industries for water treatment, soap production, plastics, paper manufacturing, and other chemical industries.Keywords: Chlorine gas, sodium hydroxide, salt, purification, electrolysis.